Chronic retained esophageal foreign body: a case report - Chhabra, Gurpreet Singh; Grover, Anumeet Singh; Kaur, Gagandeep (International Journal of Contemporary Pediatrics, 2021)
Chronic esophageal foreign bodies (CEFB) are associated with a high incidence of morbidity and mortality in adults. However, the presentation, management and outcome of chronic esophageal foreign bodies in children are not well described. Seventy-six percent of patients presented with a primary complaint of respiratory symptoms, with respiratory distress being the most common followed by asthmatic symptoms and cough. Twenty-two percent of patients had primarily gastrointestinal symptoms including nausea, vomiting and dysphagia. We present a case report of 2year 6month old male with 3 months history of cough and vomiting later diagnosed to be a case of upper esophageal foreign body impaction.